PREVALENSI LEPTOSPIROSIS PADA SAPI POTONG DI KECAMATAN SEYEGAN, MOYUDAN, DAN MINGGIR KABUPATEN SLEMAN - , MARLINDA DWI WAHYU RATNANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Leptospirosis is a zoonotic disease which widely spread in the tropical area . In 2010, the leptospirosis outbrake was occurred in Sleman regency, and the incidences were continues in high level for several years. Leptospirosis is caused by bacteria of Leptospira that can infect not only humans, but also livestock, pets and wild animals . Leptospira was divided into two species, L interrogans (250 serovar) and L biflexa (serovar 65). Type of Leptospira serovar which is dominant in one region, may different with the other regions. Serovar was also known as ones factors which can determine the severity of leptospirosis. The aims of this study was to clarify the prevalence of leptospirosis and type of leptospira serovar in beef cattle in the district of Seyegan, Moyudan and Minggir of Sleman regency. Total of 147 beef cattles from three districts were used as samples. Ten milliliters of blood were drawn from the jugular vein by venoject tube. Serum were separated for Microscopic Agglutination Test ( MAT ) using serovar of: ictero haemorrhagiae, javanica, celledoni, canicola, ballum, pyrogenes, cynopteri, rachmati, australis, pomona, grippotyphosa, hardjo, bataviae, and tarrasovi that were conducted in Bbalitvet Bogor . The principle of MAT is reaction of living leptospira serovar (antigen) with serum samples (antibody) in several dilution levels. The MAT results is positive if agglutination occur in 50 % dilution of 1 : 100 or more . The research results show that 27 samples (15 from Seyegan district, 10 from Moyudan district and 2 from Minggir district) is positive for one or two serovars. Samples are positive for serovar of hardjo (16 samples), pyrogenes (2 samples), javanica (2 samples), ichterohaemorrhagiae (5 samples), bataviae (3 samples), canicola (2 samples), and rachmati serovar (1 sample). From the results it can be concluded that : (1) The prevalence rate of cattle in the Seyegan district was 22.38 %, Moyudan district was 20.41 % and Minggir district was 6.45 %. (2) The prevalence rate of livestock in Seyegan district was 29.54 %, in Moyudan district was 25.92 % , and in Minggir district was 15.38 %. (3) Serovar were detected in three districts : hardjo 50 %, pyrogenes 6%, javanica 6%, ichterohaemorrhagiae 16 % , bataviae 10 %, canicola 6 %, and serovar rachmati 3 %. It is advised to apply precautions and treatment programs on leptospirosis infected areas, continuosly.